WEBSITE PEMESANAN DAN PEMBAYARAN TIKET BIOSKOP DENGAN FITUR SMS NOTIFIKASI PADA XXI KOTA GORONTALO - Farid (Journal Of Software Engineering And Communication, 2025)
The manual ticket booking process often leads to several issues, such as long queues, data entry errors, limited-service hours, and the risk of tickets being sold out for customers who come directly to the cinema. Moreover, the absence of an integrated online system makes it difficult for prospective viewers to access real-time information on movie schedules and seat availability. This situation reduces both the convenience and efficiency of service for customers. The research method used is a descriptive method by collecting data directly from the research location. Therefore, the author seeks to offer a solution by developing a new system, an online cinema ticket booking and payment system. The system is tested using both White-box testing and Black-box testing methods. As a result, all system functions were found to operate correctly and as expected